Effects of combustible cigarettes and electronic nicotine delivery systems on immune cell‐driven inflammation: Evidences from diabetic patients and multiple low dose streptozotocin‐treated diabetic mice - Kastratovic, Nikolina; Arsenijevic, Aleksandar; Harrell, Carl Randall; Mladenovic, Violeta; Djukic, Aleksandar; Volarevic, Ana; Jovanovic, Dalibor; Zdravkovic, Marija; Macut, Jelica Bjekic; Djonov, Valentin; Volarevic, Vladislav (Journal of biochemical and molecular toxicology, 2024)
Considering detrimental impacts of combustible cigarettes (CCs) on the exacerbation of diabetes mellitus (DM), a significant number of DM patients have substituted CCs with electronic nicotine delivery systems (ENDS). Herewith, we compared CCs and ENDS‐dependent modulation of immune cell‐driven inflammation in DM patients who used ENDS (DMENDS), CCs (DMCC) or were non‐smokers (DMAIR), paving the way for the better understanding of ENDS‐induced biological effects. Multiple low dose streptozotocin (MLD‐STZ)‐induced mice model of DM was used to support clinical findings. Both CCs and ENDS aggravated MLD‐STZ‐induced DM. Pancreatic injury and inflammation were more severe in CC‐exposed than in ENDS‐exposed diabetic mice. CCs promoted activation of NLRP3 inflammasome, enhanced production of inflammatory cytokines in neutrophils, macrophages and remarkably improved antigen presenting capacity of dendritic cells which resulted in the expansion of TNF‐α, IFN‐γ and IL‐17‐producing Th1 and Th17 lymphocytes, NK and NKT cells. Compared to CCs, ENDS more intensively promoted expansion of FoxP3‐expressing, IL‐10‐producing NK and NKT cells and triggered less intense systemic inflammatory response in diabetic animals. Similar findings were observed in DM patients. The highest numbers of inflammatory, TNF‐α and IL‐1β‐producing neutrophils and monocytes, TNF‐α and IFN‐γ‐producing T lymphocytes, NK and NKT cells were determined in the blood of DMCC patients, while total number of immunosuppressive, TGF‐β‐producing CD3 + CD4 + T cells was the highest in the blood of DMENDS patients. In conclusion, although both CC and ENDS aggravate on‐going inflammation in DM, ENDS have weaker capacity to induce production of inflammatory cytokines in immune cells than CCs. Both cigarettes (CCs) and electronic nicotine delivery systems (ENDS) modulate migration, activation and effector functions of immune cells, affecting progression of diabetes mellitus. Compared to ENDS, CCs more efficiently increase production of inflammatory cytokines in neutrophils, monocytes, T, NK and NKT cells and enhanced antigen‐presenting properties of dendritic cells, resulting in the aggravation of immune cell‐driven inflammation in diabetes.